The influence of cultural beliefs and practices on latrine access and utilization in Awerial County, South Sudan. A cross-sectional study. - Abdalla, Abdalla Benard Oliver James; Mubiru, Denis; kateregga , salongo (Student’s Journal of Health Research Africa, 2025)
Background. Lack of latrines remains a widespread health and environmental hazard in many developing countries. The study aims to assess the influence of cultural beliefs and practices on latrine utilization in Awerial County, South Sudan. Methodology. A Descriptive Analytical study design was utilized for the study. Awerial County was purposively selected based on its low latrine coverage within the state. Systematic random sampling of households was conducted. Quantitative data were collected from 384 community members who were interviewed using a structured household questionnaire. Qualitative data were collected through Focused Group Discussions and Key Informant Interviews. Findings are presented as numerical summaries, tables, and charts. Results. Majority of household heads are female 76.3% (293), 66.1% (254), reported that they do not have a latrine in their homes, a significant portion of respondent’s lack knowledge (mean 2.02, 29.7%) and resources (49.2%) for latrine usage, cultural beliefs (10.9%) was, perceived as influential, Cultural practices hindering latrine use are rare (0.5%), and responsibilities for latrine maintenance are shared among children, women, men, and others. Pearson correlation coefficient of -0.396 suggests a moderate negative correlation, meaning that as the lack of resources and knowledge about latrine construction increases, the probability of having a latrine decreases. The p-value (Sig. = 0.000) confirms that this result is statistically significant, meaning the observed relationship is unlikely to be due to chance. Conclusion The findings from Awerial County underscore the critical interplay between cultural beliefs, gender dynamics, environmental challenges, and the effectiveness of sanitation interventions to address factors like the lack of availability of resources and knowledge for latrine construction. Recommendation The study suggests creating campaigns to dispel myths and misconceptions, and providing resources and knowledge for latrine construction as one of the most important approaches to improve sanitation.